PENGEMBANGAN LEMBAR KERJA SISWA BERBASIS PROBLEM BASED LEARNING PADA MATERI VIRUS KELAS X SMA - Vivi Yana; Kurnia Ningsih; Reni Marlina (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
Abstract This research aimed to determine the validity of Problem Based Learning-based Student Worksheets on virus material and the students’ responses to it. The method used in this study was Research and Development with procedures referring to the research and development of Borg and Gall where in the process of implementation has been modified into 7 step namely research and information collecting, planning, develop preliminary form of product, preliminary field testing, preliminary product revesion, main field testing, and operasional product revision. This research had been done in three schools, namely SMAN 1 Sungai Raya, Kemala Bhayangkari High School and MA Darul Ulum with research subjects as many as 9 students in the initial field trial and 36 students in the field trial. The instruments used consisted of LKS validation sheets and student response questionnaires. The value of Problem Based Learning-based Student Worksheets validity on virus material of 0.94 which is considered to be very high. Preliminary field testing values of 83,17% with a very strong category. Main field testing values of 84.59%. overall the Problem Based Learning-based Student Worksheets is eligible to use as a teaching media on virus material dan got a strong category response. Keywords: Development Research, Student Worksheets (LKS), Problem Based Learning, Student Response, Viruses